The Role of Motivation in Mediating the Influence of Organisational Culture, Work Discipline and Leadership Style on Employee Performance - Vivi Yuliyantikarini; Djatmiko Noviantoro; Sari Sakarina (Journal of Economics and Social Sciences (JESS), 2026)
This study examines the mediating role of motivation in the relationship between organisational culture, work discipline, leadership style, and employee performance at the Central Bureau of Statistics of South Sumatra Province. This study used a quantitative approach with a survey method involving state civil servants as respondents. Data were analysed using Partial Least Squares–Structural Equation Modelling (PLS-SEM). The results showed that organisational culture, work discipline, and leadership style influenced motivation. Furthermore, organisational culture, work discipline, leadership style, and motivation also influenced employee performance. Motivation partially mediated the relationship between organisational culture and employee performance, as well as between work discipline and employee performance. It also partially mediated the relationship between leadership style and employee performance. These findings confirm that the integration of a healthy organisational culture, consistent work discipline, and an effective leadership style is a key factor in building a productive work environment and supporting continuous employee performance improvement.